Are two-person checks more effective than one-person checks for safety critical tasks in high-consequence industries outside of healthcare? A systematic review. (January 2023) - McMullan, Ryan D.; Urwin, Rachel; Wiggins, Mark; Westbrook, Johanna I.
Abstract: Double-checking has been used in high-consequence industries for decades. We aimed to determine the strength of the evidence-base regarding the effectiveness of double-checking which underpins its widespread adoption. We searched for quantitative studies of the effectiveness of two-person checking in industry sectors, excluding healthcare. We performed a systematic literature search across six databases and hand-searched key journals. We completed a narrative synthesis and quality assessment of the nine studies identified. Most studies were of fair quality. Two examined the use of two-person checks in aviation, three investigated tasks in chemical manufacturing, and four studies in psychology involved proofreading and visual search tasks. All studies found that the performance of two-people checking was not superior to that of one-person in detecting errors. Further research to compare the effectiveness of different checking processes along with factors which may support optimisation of safety checks in high-consequence industries is required. Highlights: Double-checking policies are used extensively in high-consequence industries. The evidence-base for the effectiveness of double-checking is small. Studies did not demonstrate superiority of two-person checking for error detection.